2016
DOI: 10.1080/2162402x.2016.1253655
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptome of lung tumor-infiltrating dendritic cells reveals a tumor-supporting phenotype and a microRNA signature with negative impact on clinical outcome

Abstract: Targeting immunomodulatory pathways has ushered a new era in lung cancer therapy. Further progress requires deeper insights into the biology of immune cells in the lung cancer micro-environment.Dendritic cells (DCs) represent a heterogeneous and highly plastic immune cell system with a central role in controlling immune responses. The intratumoral infiltration and activation status of DCs are emerging as clinically relevant parameters in lung cancer.In this study, we used an orthotopic preclinical model of lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 61 publications
2
47
0
Order By: Relevance
“…129 CD103 + DCs alone appear to orchestrate the appropriate Th17 response to fungal infection through production of IL-2 and IL-23. 131,132 Cell-tracking experiments in murine melanoma tumour models show that CD103 + DCs are the only intra-tumoral myeloid cell type able to transport and present intact antigen to tumour-specific CD8 + T cells and their activation was protective against tumour re-challenge. DCs take up necrotic and apoptotic tumour fragments to present to antigen-specific cytotoxic and helper T cells, and are therefore important providers of protective anti-cancer immunity.…”
Section: Dendritic Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…129 CD103 + DCs alone appear to orchestrate the appropriate Th17 response to fungal infection through production of IL-2 and IL-23. 131,132 Cell-tracking experiments in murine melanoma tumour models show that CD103 + DCs are the only intra-tumoral myeloid cell type able to transport and present intact antigen to tumour-specific CD8 + T cells and their activation was protective against tumour re-challenge. DCs take up necrotic and apoptotic tumour fragments to present to antigen-specific cytotoxic and helper T cells, and are therefore important providers of protective anti-cancer immunity.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…DCs take up necrotic and apoptotic tumour fragments to present to antigen-specific cytotoxic and helper T cells, and are therefore important providers of protective anti-cancer immunity. 130,131 The importance of DCs in lung cancer is demonstrated by ongoing efforts to harness these cells for therapeutic purposes. 133 However, these cells are rare and transcriptomic analysis of lung cancers and peritumoral tissues from mice demonstrate that the majority of infiltrating myeloid cells are actually CD11b + DCs.…”
Section: Dendritic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In murine models adoptive transfer tumourspecific CTL leads to tumour eradication in WT mice, whereas transfer of CTL to CD40 deficient mice did not lead to an effective anti-tumour immune response. 22 Tertiary lymphoid structures (TLSs) or the local TDLN provides sites for tumor antigen crosspriming by DCs in an environment sheltered from tumor-derived inhibitory molecules and cytokines ( Figure 3). 21 Furthermore, other studies have indicated that lung tumor-infiltrating CD11b + DCs strongly overexpress PD-L1, contributing to immunosuppression and tumor growth.…”
Section: Antigen-presenting Cellsmentioning
confidence: 99%
“…studies have indicated that lung tumor-infiltrating CD11b + DCs strongly overexpress PD-L1, contributing to immunosuppression and tumor growth. 22 Tertiary lymphoid structures (TLSs) or the local TDLN provides sites for tumor antigen crosspriming by DCs in an environment sheltered from tumor-derived inhibitory molecules and cytokines ( Figure 3). 13 Recent research has indicated that TLSs are critical in shaping the antitumor immune response, favouring a Th1 cell phenotype.…”
Section: Antigen-presenting Cellsmentioning
confidence: 99%